2008
DOI: 10.1080/10401330802199542
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of Medical Students With Voluntary Use of Personal Data Assistants for Clerkship Assessments

Abstract: Before asking students and clinical supervisors to use a PDA-based encounter-evaluation form in clerkship, planners should conduct a careful assessment of the advantages and disadvantages for students of the system they hope to implement. The prima facie greater convenience and efficiency of the PDA may actually be offset by workplace disincentives and inefficiencies in data recording, relative to the incentives and efficiencies associated with a system based on printed (paper) forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…A majority of preceptors felt that further faculty development would have been helpful in preparing them for the use of the eClinic Card, their approach to coaching, and providing feedback to students. Cendan et al [18] also found that faculty development was important in introducing mobile workplace-based assessment, and Norman et al [19] found preceptors were unfamiliar with the use of personal digital assistants for workplace-based assessment, and many lacked confidence in the technology. According to Sandars and Dearnley [20], training is essential for all users when introducing mobile work-based assessment and should be provided in a variety of formats (face-to-face and online).…”
Section: Critical Reflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of preceptors felt that further faculty development would have been helpful in preparing them for the use of the eClinic Card, their approach to coaching, and providing feedback to students. Cendan et al [18] also found that faculty development was important in introducing mobile workplace-based assessment, and Norman et al [19] found preceptors were unfamiliar with the use of personal digital assistants for workplace-based assessment, and many lacked confidence in the technology. According to Sandars and Dearnley [20], training is essential for all users when introducing mobile work-based assessment and should be provided in a variety of formats (face-to-face and online).…”
Section: Critical Reflectionmentioning
confidence: 99%
“…Several authors have reported the importance of functionality and ease of use with the introduction of mobile workplace-based assessment systems [ 12 , 13 , 18 , 19 ], and recent work [ 21 ] has also confirmed ease of use and intuitiveness of a mobile app to capture data on entrustable professional activities in postgraduate workplace-based assessment [ 20 ]. In our study, students were satisfied with the use of the mobile app and found it dependable and easy to use.…”
Section: Critical Reflectionmentioning
confidence: 99%
“…En el primero de ellos, Torre et al [18] mostraron que el uso de estos instrumentos facilita el registro de la información. No obstante, Norman et al [40] no tuvieron éxito siguiendo la misma estrategia; explicaron esta discrepancia por el hecho de que en la experiencia de Torre et al [18], el empleo de las PDA fue obligatorio y los estudiantes sólo completaron dos evaluaciones en cada rotación. Como este número parece insufi ciente para obtener una fi abilidad adecuada, parecía que la PDA no tenía una adecuada fi abilidad en este contexto.…”
Section: Aplicación De La Tecnología Y Otros Ejemplos De Mejoras En Eunclassified
“…In October 2010, another study showed that 85% of all American adults, 96% of those were aged 18-29 years, and 90% of those aged 30-49 years own a cell phone (Smith 2010a). Work has previously been done looking at the trends of handheld computing and mobile device use in graduate medical education (Barrett et al 2004;Sutton et al 2004;Mattana et al 2005;Khan et al 2007;Morris et al 2007), with undergraduate medical students (Grasso et al 2005;Kho et al 2006;Kennedy et al 2008;Norman et al 2008;Chatterley & Chojecki 2010;Ferenchick et al 2010;Lasserre et al 2010), and the health care setting (Garritty & El Emam 2006;Ranson et al 2007;Trelease 2008;Evans & Stacey 2009). Looking specifically at medical students, Grasso et al (2005) surveyed preclinical and clinical medical students and found that the clinical students used drug references and medical calculators on their handheld device.…”
Section: Introductionmentioning
confidence: 99%